Future Harvest Programme for Musa in Africa - Ortíz, R.; Frison, Emile A.; Sharrock, S. (2002)
The private sector has been involved in the production and marketing of production inputs such as seeds (Premier, A1heri, UAC), fertilizers (Dangote, Golden), implements John Holt, Saulawa Machinery), agrochemicals (CAPL Rhone Total, etc.) in the state. This sector is also involved in the purchase of farm produce for industrial (flour. food, beverages, etc.) processing and supports commodity research and extension. A greater involvement of the private sector in the manufacture of prototype technologies should be facilitated. There is poor market information network in the state. Proper documentation of market places, input marketers, output markets, processors} industries, and NGOs should be carried. out. The use of radio in MIS should be intensified. Local government areas should facilitate the establishment of information centers in market places. Prinred materials should be produced in simple pictorial forms in local languages. A Market Information Systems website/network for use by all stakeholders should be developed. Finally, training needs have been identified for farmers, suppliers/marketers. fabricators, and processors in support of market driven-technology transfer and commercialization.